Endocrine Complications in Pediatric Beta-Thalassemia Major Patients: A Single-Center Experience - Yenigurbuz, Fatma Demir; Akıncı, Burcu; Üstyol, Ala; Ökdemir, Deniz; Sezer, Ahmet (Harran Üniversitesi, 2022)
Background: Our aim was to identify risk factors and clinical correlates of endocrine complications in ?-thalassemia major (BTM) patients.Materials and methods: This was a retrospective study carried out in the pediatric hematology and pediatric endocrinology departments of a tertiary healthcare institution with the medical data of 249 children with BTM (108 females, 43.4%; 141 males, 56.6%) with a median age of 7.17 (2 -17.8) years. Baseline descriptive, clinical features including endocrine complications and laboratory data were noted. Correlation between the presence of endocrine complications and demographic, clinical, and laboratory variables were sought. The effects of age, gender, race, height, weight, and splenectomy on endocrine complications were evaluated separately in each complication group. Results: Vitamin D deficiency/insufficiency is the most common endocrine complication (41.7%). According to Turkish children, Syrian children had also significantly lower vitamin D concentration (p=0.001). At least one endocrinopathy was reported in the majority of BTM patients (67.9%). Accordingly, pubertal status (p=0.014) and Syrian nationality (p=0.007) had significant impacts on TSH levels. Syrian children and those with delayed puber-ty had greater likelihood for subclinical or evident hypothyroidism. The likelihood of suffering from at least one endocrine complication was higher in older children (p=0.042) and those with Syrian nationality (p=0.025)Conclusion: Disorders of endocrine and metabolic nature are common in children with BTM. Early detection and protocol-based multidisciplinary management of these disorders constitute the most suitable strategies to in-crease patients' quality of life. Surveillance, early detection and treatment, and collaborative follow-up with a multidisciplinary team are the key points in the reduction of the severity and frequency of endocrine complica-tions as well as optimization of therapeutic outcomes.

Background: We aimed to investigate the risk factors and clinical correlates of endocrine complications in ?-thalassemia major (BTM) patients. Materials and methods: This retrospective study was performed in the pediatric hematology and pediatric endocrinology departments of a tertiary care center using data derived from medical records of 249 children with BTM (108 females, 43.4%; 141 males, 56.6%) with a median age of 7.17 (range: 2 to 17.83) years. Baseline descriptive, clinical features including endocrine complications and laboratory data were noted. Correlation between the presence of endocrine complications and demographic, clinical, and laboratory variables were sought. Results: The majority of BTM patients (n=169, 67.9%) had at least one endocrine complication. Syrian patients had lower levels of vitamin D and were more likely to have subclinical hypothyroidism. Patients with advanced age, delayed puberty, Syrian nationality, and short stature were more likely to suffer from at least one endocrine complication. Conclusion: Endocrine and metabolic disorders are very common in children with BTM. Early detection of these disorders, as well as multidisciplinary management with standardized protocols constitutes the most suitable strategy to provide a better quality of life for these patients. Regular surveillance, early diagnosis, treatment, and follow-up with the collaboration of a multidisciplinary team are the key points in the reduction of the severity and frequency of endocrine complications as well as optimization of therapeutic outcomes.
Pediatrik Beta Talasemi Major Hastalarında Endokrin Komplikasyonlar: Tek Merkez Deneyimi
Keywords: Clinical Sciences; Klinik Tıp Bilimleri